A Brief Environmental Analysis of Tourism and Hotel Industries and their Impact on Nepalese Base Structure - Karki, Govinda Bahadur (KMC Research Journal, 2018)
This brief academic research paper deals with the evolution and present status of tourism and hotel industry in Nepal. It also incorporates the description about tourism business enterprises, about hotel industries, legal and regulatory framework, and contribution of tourism and hotel industries in country's Gross Domestic Product and the impact of tourism and hotel industries on socio-cultural, economic, political and cultural sectors. The basic thrust of this research paper to analyze environmental/ opportunities analysis of tourism and hotel industries as per the rules, policies and market structures. Domestic and global tourism is now generally considered as one of the largest industries in the world and one of the most significant sources of employment and GDP.